Vascular Healing of a False Lumen After Bioresorbable Scaffold Implantation. (February 2016) - Kawamoto, Hiroyoshi; Jabbour, Richard J.; Tanaka, Akihito; Latib, Azeem; Colombo, Antonio
Abstract : Supplemental Digital Content is available in the text.